Pancasilah Based Dakwah Communication Model in the Era of Hyperreality - Fadhli, Muhammad fadhli muttaqien (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research aims to discover and explore the Pancasila-based da'wah communication model in the hyperreality era. This research uses qualitative methods based on results from the literature. Pancasila is a state philosophy that must be disseminated as an ideology. However, the distribution process must be done with more than simple steps. Creating a particular form of communication that can run effectively and efficiently is necessary. Pancasila-based da'wah communication is appropriate because it has a significant influence. Because the da'wah narrative that was initially conveyed only used an Islamic perspective, this time it was developed using the Pancasila basis. In da'wah communication, there are bil hall, bil kolam, and bil hal models of da'wah communication, which, in the end, after being integrated between da'wah and Pancasila communication, gave birth to a Pancasila-based model of da'wah communication with five keywords, namely divinity, humanity, unity, deliberation, and justice.